Pemikiran Hukum Islam Abdurrahman Wahid: Harmonisasi Islam Dan Budaya - Damanik, Muhammad Zein; Sitorus, Intan Lestari; Sintia, Winda Dwi (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2024)
This research discusses Abdurrahman Wahid's Islamic legal thinking, which is known for its harmonization approach between Islamic values ​​and local culture. The background of this research is rooted in the challenges of implementing Islamic law in Indonesia, where cultural plurality is an important factor in building justice and social harmony. Abdurrahman Wahid, or Gus Dur, offers a progressive view that prioritizes openness to local traditions as an integral part of the interpretation of Islamic law. This research uses library research methods by examining the works of Abdurrahman Wahid, academic literature and other relevant documents. A descriptive-analytical approach is applied to understand Gus Dur's ideas about the relationship between Islamic law and culture, as well as its significance in the Indonesian socio-political context. The research results show that the harmonization of Islam and culture according to Abdurrahman Wahid is an effort to bridge the universality of Islamic teachings with local diversity. This concept emphasizes the importance of inclusiveness and respect for culture in the application of Islamic law, which is relevant in realizing harmony and justice in a pluralistic society